2009
DOI: 10.1037/a0014136
|View full text |Cite
|
Sign up to set email alerts
|

Priming of familiar and unfamiliar visual objects over delays in young and older adults.

Abstract: Although priming of familiar stimuli is usually age invariant, little is known about how aging affects priming of pre-experimentally unfamiliar stimuli. Therefore, this study investigated the effects of aging and encoding-to-test delays (0 min, 20 min, 90 min, and 1 week) on priming of unfamiliar objects in block-based priming paradigms. During the encoding phase, subjects viewed pictures of novel objects (Experiments 1 and 2) or novel and familiar objects (Experiment 3) and judged their left/right orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 57 publications
6
24
0
Order By: Relevance
“…Unlike the younger adults, older adults did not exhibit either the FN400 or the N300, suggesting that they did not experience fluency that could have informed their behavioral responses. Although older adults exhibit intact priming (Fleischman, 2007), they may rely on long-term semantic representations (e.g., everyday objects or easily labeled colors) for visual priming (Soldan, Hilton, Cooper, & Stern, 2009), which would not have been activated in the present study. As with the dual-process model, the fluency heuristic model would interpret the late-stage neural activity in older adults as a failure to activate a familiarity or recollection process, but as successful activation of postretrieval monitoring and verification processes.…”
Section: Discussionmentioning
confidence: 67%
“…Unlike the younger adults, older adults did not exhibit either the FN400 or the N300, suggesting that they did not experience fluency that could have informed their behavioral responses. Although older adults exhibit intact priming (Fleischman, 2007), they may rely on long-term semantic representations (e.g., everyday objects or easily labeled colors) for visual priming (Soldan, Hilton, Cooper, & Stern, 2009), which would not have been activated in the present study. As with the dual-process model, the fluency heuristic model would interpret the late-stage neural activity in older adults as a failure to activate a familiarity or recollection process, but as successful activation of postretrieval monitoring and verification processes.…”
Section: Discussionmentioning
confidence: 67%
“…Several longitudinal studies have demonstrated stable priming with advancing age despite substantial declines in explicit memory (Hultsch et al, 1992; Christensen et al, 1997; Davis et al, 2001; Fleischman et al, 2004). Moreover, many cross-sectional studies employing a range of different tasks have reported non-significantly different priming between groups of young and older adults (e.g., Mitchell et al, 1990; Light et al, 1992; Park and Shaw, 1992; Schacter et al, 1992; Mitchell and Bruss, 2003; Wiggs et al, 2006; Soldan et al, 2009; Spaan and Raaijmakers, 2011). …”
Section: Explicit and Implicit Memory In Normal Agingmentioning
confidence: 99%
“…Thus, when the original non-matching possible and impossible stimuli developed by Schacter and Cooper were used with the same experimental design as that of Experiment 1, Soldan, Hilton et al (in press, Experiment 1) found the typical pattern of results: priming for possible objects and nil priming for impossible objects. Given that the only procedural difference between these two experiments was the addition of the matched objects during the test phase in Experiment 1 of this study, the negative priming effect for old impossible objects in Experiment 1 might be attributable to the fact that the matched objects reduced the putative influence of explicit memory on task performance, as postulated by Ratcliff and McKoon (1995) and Williams and Tarr (1997).…”
Section: Discussionmentioning
confidence: 79%
“…By comparison, the set of impossible objects (N = 152) from which Schacter and Cooper chose their stimuli consisted of approximately 13%, 28%, and 59% of stimuli with 1, 2, and 3+ structural violations. Likewise, Experiment 1 by Soldan, Hilton et al (in press), which used the original Schacter and Cooper stimuli with the same design as the present study, the proportion of impossible objects (N=48) with 1, 2, and 3 or more structural violations was 13%, 29%, and 58%, respectively. This change in the composition of the impossible stimuli was unavoidable because we desired a similar proportion of objects with 1, 2, or 3 structural violations in order to test the predictions of the structure-extraction bias model.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation